The Status of Theory in the Study of Literature and the Visual Arts - Kučeković, Filip (Poznańskie Studia Slawistyczne, 2025)
The article compares the state of theory in literary studies and the visual arts. While in the one the end of theory is proclaimed for several decades, in second it is systematically neglected as insufficiently scientific. A critique of the existing methods of art history, which are predominantly based on documentation and historiography in the study of artworks is needed. Discipline is demoted to an auxiliary historical science, which results in its vanishing. An example is given of the research of Didi-Huberman, who, by establishing the difference between the visible and the visual, extends the field of study of the visual arts with his theory, thereby prolonging its life and ensuring that the end of art history, which the discipline itself has been questioning for several decades, is avoided. The paper argues for openness and the overcoming of boundaries within two humanities disciplines that have begun to distance themselves from each other and neglect their mutual contributions.